Unveiling Melodies: Navigating Issues in African Oral Literature through Nkem Okoh's Preface to Oral Literature - Anasiudu, Okwudiri (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
The oral literature in Africa has not been taken seriously. The implication is that assertion is a fear of its death as many scholars in Africa have given it less attention. To address the gap and deepen the conversation, this study explored Nkem Okoh's Preface to Oral Literature shedding light on its perspective on the ongoing discussions about oral literature in Africa. The goal is to offer a detailed understanding and assessment of African oral literature, using this text as a case study. The analysis relies on postcolonial criticism and a qualitative research approach. Two key questions guide the research: How does Preface to Oral Literature contribute to debates on the form and nature of oral literature in Africa, especially concerning identity reclamation and anticolonialism? How does it criticize Euro-western scholars and their distorted views of Africa as a dark continent, contributing to the wider discourse on oral literature in Africa? The findings highlight challenges in the study of African oral literature, including issues related to naming, etymology, nomenclature, the fundamental nature of oral literature, discussions on aligning it with folklore, ownership and royalty dynamics, and the debate between evolutionist and relativist perspectives. The impact of Western biases on the analysis of African oral literature and challenges linked to understanding the consequences of the changing global literary landscape on the status of oral literature in Africa are also emphasized. The study recommends for further research, the need for a comparative analysis and assessment of the contemporary impact of oral literature in African societies.